A study on evaluating financial performance: a case of Kumpulan Perangsang Selangor Berhad / Siti Salwa Mohd Isa - Mohd Isa, Siti Salwa (2012)
Establish on 11 August 1975, Kumpulan Perangsang Selangor Berhad was listed on the Main Board of Bursa Malaysia Securities Berhad on 22 July 2003. Perangsang Selangor is the leading integrated provider of Infrastructure and Utility services in the State. The researcher carried out the study with the objective of finding out the financial performance of KPS for the financial year 2005-2010. The researcher carried out the study with analytical type of research design with the help of secondary data collection method. For this purpose the researcher took past six years financial statements into consideration. The data is checked out for the validity and reliability before conducting the study. The researcher used ratio analysis as a financial tool to reveal the firm’s financial performance. Ratios involved are profitability, capital structure, liquidity and activity ratio. Ratios help to summarize large quantities of financial data to make quantitative judgment about the financial performance of the firms. Those areas are looking forward to measure the firm management efficiency and insolvency, thus reveal the management strengths and weaknesses. This project studies would be useful to the company and also to the researches as reference to the management to improve their performance and also as a guide to the researcher to improve research skills and doing research into other major area in near future.